Pengaruh Price Dan Social Media Marketing Activities (SMMA) Terhadap Healthcare Apps Purchase Intention Dimediasi Oleh Consumption Values - Claudia Alverina; Hendra Achmadi (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
The increasing use of social media in Indonesia opens up opportunities for entrepreneurs especially in the health sector on COVID-19 pandemic era. During the COVID-19 pandemic, the need for online health services has soared. According to data from the Global Web Index (GWI) social media users in Indonesia in 2022 increased by 12.6% in the past year. The number of rivalries between health facilities is getting tougher, so a specific strategy is needed in marketing techniques in the field of health services in Indonesia. Market price competition is also one of the problems in the business sector. In this study, 163 samples collected had purchased health care products on the MySiloam application belonging to Siloam Hospital Group. The sample was obtained by purposive sampling method and then the data was processed using the PLS-SEM analysis method with the SmartPLS ver 3.2.9 application. The results obtained from data processing, there are several hypotheses that do not show a relationship between research variables, but social media marketing activities (SMMA) have the strongest influence on epistemic value which then increases healthcare apps purchase intention. Suggestions for further research should be done with a wider number of samples and tighten the criteria for respondents so that the data obtained is more significant and accurate.